Evaluation and adaptation of a two-way text messaging intervention in the WIC breastfeeding peer counseling program: A qualitative analysis - Josefa L. Martinez-Brockman; Josephine R. Granner; Brice Buchanan; Lisbette Acosta; Marilyn Lonczak; Lori Goeschel; Xiao Xu; Leslie Curry; Marcella Nunez-Smith; Rafael Pérez-Escamilla (PLoS ONE, 2025)
Breastfeeding (BF) is vital for maternal and infant health, yet post-hospital discharge support remains a challenge. The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides BF peer counseling prenatally and up to 1-year postpartum among low-income women in the United States. The Lactation Advice Through Texting Can Help (LATCH) intervention is an evidence-based two-way text messaging intervention that provides BF education and support in the WIC peer counseling program. The intervention is implemented by peer counselors (PCs) in the WIC program, with the supervision and support of a lactation consultant. The aim of this qualitative study was to assess the barriers and facilitators to the implementation of LATCH during the feasibility trial and to investigate strategies for adapting and scaling up the intervention. In-depth interviews with LATCH and PC program key informants aimed to evaluate the intervention and explore its adaptation and scale-up. Interviews were analyzed using line by line inductive thematic analysis. Findings were mapped to the Model for Adaptation Design and Impact (MADI) framework to describe the proposed adaptations, and to the Program Impact Pathways (PIP) framework to identify causal pathways and critical quality control points. Results demonstrate that LATCH facilitates continued engagement between PCs and WIC mothers; however, implementation feasibility issues remain. Suggested adaptations to LATCH include the use of an integrated comprehensive platform, ensuring continuity of care through an expanded spectrum of communication options, the need to develop a PC support model for “off hours” (non-business hours), and the need to obtain local WIC office management’s buy-in for the communications platform and the off-hours PC model. Critical quality control points were identified when results were mapped to the MADI and PIP frameworks. Implementing these changes has the potential to expand access to BF peer counseling support and improve BF equity among low-income women.